2009
DOI: 10.1590/s0103-50532009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, trypanocidal activities and physicochemical parameters of nor-²-lapachone-based 1,2,3-triazoles

Abstract: A atividade citotóxica de cinco derivados 1,2,3-triazólicos da nor-β-lapachona e do precursor azidonaftoquinona, foi avaliada contra seis linhagens de células neoplásicas: SF-295 (sistema nervoso central), , MDAMB-435 (melanoma), HL-60 (leucemia), PC-3 (próstata) e B-16 (melanoma murino). Valores de IC 50 entre 0,43 e 9,48 μM foram obtidos. A 3-(4-(1-hidróxicicloexil)-1H-1,2,3-triazol-1-il)-2,2-dimetilnaftol[1,2-b]furan-4,5-dione apresentou-se altamente citotóxica contra MDAMB-435, com IC 50 menor do que o enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Since the synthesis of arylamino substituted lapachones and azidoquinones are well established in our group [25,40,42], compounds 13 and 14 were prepared as shown in Scheme 3. Following click methodology, compounds 13 and 14 were reacted with selenium-containing azide and alkyne, respectively, to furnish the naphthoquinones 15 and 16 in 70% and 80% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the synthesis of arylamino substituted lapachones and azidoquinones are well established in our group [25,40,42], compounds 13 and 14 were prepared as shown in Scheme 3. Following click methodology, compounds 13 and 14 were reacted with selenium-containing azide and alkyne, respectively, to furnish the naphthoquinones 15 and 16 in 70% and 80% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nor-β-lapachone and derivatives are among the most potent compounds from the lapachol group [25,26]. Recently, we demonstrated [50] the cytotoxicity and genetic toxicity of nor-β-lapachone in human lymphocytes, HL-60 leukaemia, and immortal normal murine V79 fibroblasts ranging from 2.5 and 5 μM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although lapachol has been licensed in Brazil for general clinical practice as a carcinostatic drug (Da Silva J unior et al 2009), and several studies regarding its anticancer properties have been reported, it is stated that high doses of lapachol are required to achieve therapeutic efficacy, resulting in high side effects in patients (Sunassee et al 2013). Because of this, the use of lapachol as coadjuvant in the treatment of certain cancer types has been stopped (Hussain et al 2007).…”
Section: Introductionmentioning
confidence: 99%